Expression of Thy-1 antigen is not limited to T cells in cultures of mouse hemopoietic cells. - Schrader, J W (1982)
Large numbers of Thy-1-positive cells were observed in cultures of bone marrow cells that had been depleted of T cells and grown for 3 to 4 days in the presence of medium conditioned by concanavalin A-activated spleen cells. Cells bearing levels of Thy-1 comparable with those on the bulk of thymocytes were isolated by using the fluorescence-activated cell sorter. Although many were large blasts, the Thy-1-positive cells failed to grow in response to T-cell growth factor and concanavalin A; about one-third, however, proliferated in the presence of factors stimulating hemopoietic progenitor cells. Furthermore, the Thy-1-positive population included cells capable of forming large colonies of macrophages and granulocytes in agar and cells forming splenic colonies in lethally irradiated mice. The appearance of the Thy-1-positive cells did not correlate with the presence of either T-cell growth factor or T-cell-derived granulocyte/macrophage colony-stimulating factor. These findings indicate that Thy-1 can occur on various murine hemopoietic stem and progenitor cells and myeloid cells; Thy-1 can no longer be regarded as an unambiguous marker of commitment to the T-cell lineage.